KORUPSI ADALAH SUATU PERBUATAN TINDAK PIDANA YANG MERUGIKAN NEGARA DAN RAKYAT SERTA MELANGGAR AJARAN AGAMA - Mudemar A. Rasyidi (JURNAL MITRA MANAJEMEN, 2014)
Abstract Corruption is a criminal act that breaks and against the state law and the religion law. Due tothe fact that this corruption is not only prohibited by the greatest one God but the effectivelegislation rule as well. Furthermore, the corruption can bring about a loss to all side. Forinstance; being able to make a misery society and country, locking the country economygrowth rapidity, putting in disorder country, being able to bring about a bad image for thecountry on the international people’s view, in addition to, being able to cut down the countrythrust level on the international worl eithin doing cooperation, mainly in economy sector. Evenfor further more, the corruption make afraid of all foreigner investors to invest their stock orshare in Indonesia.On the other hand, the corruption can also induce the blocked project being carried out inourselves country as well as can hamper routine’s job of the country. Thus the corruption actcan become the cause of the stopped country advance or progress. As a final point, thosecorruptors’ re properly given a punishment dealing with their deed. Even a great deal ofsociety group wish those corruptors to be killed out or be given as a death sentence or in otherwords, at least is to be imposed as heavy as punishment in order to making them discourageto redo their deed. As a matter of the fact, this is only an example for other people who want todo what was done by the perpetrators before. In the long run, the corruption level can bedecreased in this our motherland’s country.Keywords: the corrupt criminal act constitution, constituonal law, the effectivelegislation rule, Islamic law, Al-Qur’an & Al-Hadist.